ROLE OF VIRECHANA KARMA IN DADRU (TINEA CORPORIS) - A CLINICAL STUDY - Verma Meenakshi,; Thakkar Nikunj, (International Journal of Applied Ayurved Research, 2018)
“Skin is the mirror of internal disease” the biggest blanket, the widest barriers and the strongest warrior SKIN represent the inner health and outer beauty of an individual. Skin forms a self replacing, multifunctional covering over the surface of body which isolates it forms the environment. Any disease related to skin can create physical as well as psychologi-cal problems in an individual. Skin diseases are mostly caused by infections like bacteria, fungi etc. Tinea corporis is a superficial fungal infection (dermatolophytosis of the arm and legs, especially on glabrous skin: however, it may occure on ant part of the body. it may have variety of appearances: most easily identifiable are the enlarging raised red rings with a cen-tral area of clearing. The edge of the rash appear elevated and scaly to touch, Sometimes the skin rash may be dry and flaky. Almost invariably, there will be hair loss in areas of the in-fection, Tinea infections contributes about 10-20 % of overall skin diseases. On the basis of clinical symptoms, tinea simulates with dadru kustha. In the present study, A female patient aged 27 yrs suffering from dadru since 2 month with severe itching sensation over abdominal area, burning sensation is other associated symptoms with thick radish and blackish discol-ouration with rounded margin. A case of Dadru kustha vis-à-vis tinea corporis has been treated with Shodhana i.e. Virechana. And Shamana after Shodhana 1 month of treatment with Gandhaka Rasayan, Aarogyavardhini, Samsamani Vati, Aamlaki Rasayan significant improvement has been observed in parameters like Kandu (itching), Daha (burning sensa-tion), Rookshata (dryness), Raga (erythema), Pidika (eruptions)and Utsaana Mandala (ele-vated circular skin lesion).